Late functional improvement after lacunar stroke: a population-based study - Ganesh, Aravind (J Neurol Neurosurg Psychiatry, 2018)
BACKGROUND: Recovery in function after stroke involves neuroplasticity and adaptation to impairments. Few studies have examined differences in late functional improvement beyond 3 months among stroke subtypes, although interventions for late restorative therapies are often studied in lacunar stroke. Therefore, we compared rates of functional improvement beyond 3 months in patients with lacunar versus non-lacunar strokes. METHODS: In a prospective, population-based cohort of 3-month ischaemic stroke survivors (Oxford Vascular Study; 2002–2014), we examined changes in functional status (modified Rankin Scale (mRS), Rivermead Mobility Index (RMI), Barthel Index (BI)) in patients with lacunar versus non-lacunar strokes from 3 to 60 months poststroke, stratifying by age. We used logistic regression adjusted for age, sex and baseline disability to compare functional improvement (≥1 mRS grades, ≥1 RMI points and/or ≥2 BI points), particularly from 3 to 12 months. RESULTS: Among 1425 3-month survivors, 234 patients with lacunar stroke did not differ from others in 3-month outcome (adjusted OR (aOR) for 3-month mRS >2 adjusted for age/sex/National Institutes of Health Stroke Scale score/prestroke disability: 1.14, 95% CI 0.75 to 1.74, p=0.55), but were more likely to demonstrate further improvement between 3 months and 1 year (aOR (mRS) adjusted for age/sex/3-month mRS: 1.64, 1.17 to 2.31, p=0.004). The results were similar on restricting analyses to patients with 3-month mRS 2–4 and excluding recurrent events (aOR (mRS): 2.28, 1.34 to 3.86, p=0.002), or examining BI and RMI (aOR (RMI) adjusted for age/sex/3-month RMI: 1.78, 1.20 to 2.64, p=0.004). CONCLUSION: Patients with lacunar strokes have significant potential for late functional improvement from 3 to 12 months, which should motivate patients and clinicians to maximise late improvements in routine practice. However, since late recovery is common, intervention studies enrolling patients with lacunar strokes should be randomised and controlled.